2019
DOI: 10.1021/acsmacrolett.9b00568
|View full text |Cite
|
Sign up to set email alerts
|

Tg Confinement Effect of Random Copolymers of 4-tert-Butylstyrene and 4-Acetoxystyrene with Different Compositions

Abstract: If it is the author's pre-published version, changes introduced as a result of publishing processes such as copy-editing and formatting may not be reflected in this document. For a definitive version of this work, please refer to the published version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…[30,37,38] Extensive experimental studies have focused on the T g behavior of films of linear, freely deposited polymers as a function of nanoscale confinement. [1][2][3][4][5][6][7]9,10,[15][16][17][18][19][20][21]27,30,[31][32][33][34][35][36]38] A simple yet incomplete explanation for such T g -confinement effects has been posited in many of these studies: the presence of the free surface provides additional mobility relative to bulk behavior and leads to a T g decrease in sufficiently thin films which lack significant attractive-polymer substrate interactions; when strong attractive polymersubstrate interactions exist, such as hydrogen-bonding, they may overwhelm the effect of the free surface and lead to a T g increase in films of similar nanoscale thickness. [1,2,3,5,[15][16][17][19][20][21] We note that recent molecular dynamics simulations have indicated that the spatial extent of collective motion (associated with T g ) in the free-surface interfacial region of a thin film is not altered within simulation uncertainty from the film interior, but the simulations do provide support for a large interfacial mobility gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30,37,38] Extensive experimental studies have focused on the T g behavior of films of linear, freely deposited polymers as a function of nanoscale confinement. [1][2][3][4][5][6][7]9,10,[15][16][17][18][19][20][21]27,30,[31][32][33][34][35][36]38] A simple yet incomplete explanation for such T g -confinement effects has been posited in many of these studies: the presence of the free surface provides additional mobility relative to bulk behavior and leads to a T g decrease in sufficiently thin films which lack significant attractive-polymer substrate interactions; when strong attractive polymersubstrate interactions exist, such as hydrogen-bonding, they may overwhelm the effect of the free surface and lead to a T g increase in films of similar nanoscale thickness. [1,2,3,5,[15][16][17][19][20][21] We note that recent molecular dynamics simulations have indicated that the spatial extent of collective motion (associated with T g ) in the free-surface interfacial region of a thin film is not altered within simulation uncertainty from the film interior, but the simulations do provide support for a large interfacial mobility gradient.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with bulk films of the same polymer, thin films of linear, freely deposited polymers that are a few tens of nanometers thick may exhibit significantly different properties, for example, glass transition temperature ( T g ), fragility, and stiffness among others. [ 1–48 ] For instance, in comparison with a bulk polystyrene (PS) film and as measured by ellipsometry, a 21‐nm‐thick, substrate‐supported high molecular weight (MW) PS film exhibits a T g reduction of 10°C. [ 18 ] Understanding such nanoscale T g ‐confinement effects in polymers is important for many advanced technological applications, for example, thin films used in nanolithography processes for microchip manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer films are used in a myriad of applications, including food or medical packaging, separation membrane, , polymer electrolyte fuel cells, , and so on. While most applications employ polymers in the micrometer size range, , some employ them in the nanometer size range. ,, Many studies of polymers under confinement in nanometers have found that the glass transition temperature, T g , and effective viscosity, η eff , ,, deviate from the bulk values and vary with the size of confinement. It is generally agreed that confinement causes dynamic properties to change, attributable to perturbations to the local dynamics by the confining walls or interfaces.…”
mentioning
confidence: 99%
“…Most recently, the potential of nanofilms for environmental, energy, and flexible electronic applications was demonstrated. Utilization of polymer nanofilms is thus set to become more widespread in the future. A large number of studies have found that many key properties of polymer films, such as the glass-transition temperature, T g , effective viscosity, η eff , diffusion coefficient, D , and crystallization rates, differ from their bulk values when the film thickness, h 0 , is decreased below ∼100 nm. A variety of confinement effects have been found, including depression, ,,, enhancement, ,, and constancy, , and even nonmonotonic variations , of these properties have been found for different polymer nanofilms.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the local dynamics of the polymer near an interface can play a significant role in the average property of a polymer nanofilm. , It has been broadly believed that the chain segments near the free surface are surrounded by more free volume and so may possess a higher mobility than those in the inner region of the film. ,, Experiments in support of this idea include those of Forrest and Sharp and Zuo et al, who found that the T g of polymer films became independent of film thickness and equal to the bulk T g when the films were capped by an aluminum or crystallized polymer layer that eliminated the free surface. As a result, reductions in T g , ,,, η eff , ,,, and D , with decreasing h 0 are usually ascribed to the dominance of the mobility enhancement effect of the free surface. Conversely, chain segments near a solid substrate can be pinned to the substrate surface by physical or chemical interactions, resulting in constraints in the motion of the near-substrate chains. , These substrate effects, if strong enough, can neutralize or even overwhelm the effect of the free surface.…”
Section: Introductionmentioning
confidence: 99%